Konsep Desain Taman Ramah Anak Di Taman Janggan Kota Denpasar - Puspayanti, Ayu Kade Puri; Semarajaya, Cokorda Gede Alit; Sutari, Ni Wayan Sri (Jurnal Arsitektur Lansekap, 2024)
Concept Design of Child Friendly Garden in Taman Janggan Denpasar City . Taman Janggan is one of the Child Friendly City programs which developed by government with an area of ?? 3,385 m 2 located in the Renon Denpasar. This park has a land area of ?? 1,723 m 2  which is not organized yet and enable for further development. This research aims to produce a child friendly garden concept design that can support recreational activities. The method used in this research is a survey method with data collection techniques include observation, interviews, and literature study. The research carried out by the stages consisted inventory, analysis, synthesis, concept development, and concept design. The research results are obtained an site plan, section, and perspective illustrations. The “agri curricular ” concept is an illustration of child-friendly garden concept with an agriculture theme that paying attention to user needs and comfort through the softscape and hardscape arrangement of the garden.